A ketogenic diet regulates microglial activation to treat drug addiction - Ji, Jie; Tang, Yi (Frontiers in Pharmacology, 2025)
Drug addiction is a chronic and potentially deadly disease that is considered a global health problem and describes the alteration of brain function by psychostimulant drugs through changes in the reward system. However, there is still no ideal strategy for the management of drug addiction. Previous studies have suggested that microglia are involved in events associated with neuroplasticity and memory, which are also related to drug addiction. Many studies have shown that psychoactive substances may act directly on immune cells, altering their function and inducing the production of various inflammatory mediators. In recent years, a ketogenic diet (KD) was shown to have therapeutic benefits as a dietary therapy for a variety of neurological disorders. With respect to drug addiction, studies have shown that a KD can alleviate glucose metabolism disorders caused by alcohol use disorders by increasing ketone metabolism, thereby reducing withdrawal symptoms. This finding indicates the potential of a KD as a treatment for drug addiction, since a KD may promote the transition of microglia to a predominantly anti-inflammatory state through several mechanisms. Here, we discuss recent research showing that a KD plays a variety of roles in controlling microglia-mediated inflammation, opening new treatment avenues to treat drug addiction. This succinct analysis offers evidence of the enormous potential of a KD to treat drug addiction through the inhibition of microglial activation.